INNOVATIVE EDUCATIONAL TECHNOLOGIES ARE A FACTOR IN THE MODERNIZATION OF THE EDUCATION SYSTEM (Conferencea, 2022)
The article discusses in detail the wide application of pedagogical innovations in the educational process as a global trend of global development, the growing scale of pedagogical innovations, the systematic application of innovations in education at a time when the country is rapidly developing.